Targeted pelvic constraint force induces enhanced use of the paretic leg during walking in persons post-stroke - Park, Seoung Hoon (IEEE Trans Neural Syst Rehabil Eng, 2020)
The purpose of this study was to determine whether activation of muscles in the paretic leg, particularly contributing to propulsion, and gait symmetry can be improved by applying a targeted resistance force to the pelvis in the backward direction during stance phase while walking in individuals post-stroke. Thirteen individuals post-stroke participated in two experimental sessions, which consisted of treadmill walking, with either targeted or constant resistances, together with overground walking. For the targeted condition, a resistance force was applied to the pelvis during the stance phase of the paretic leg. For the constant condition, the resistance force was applied throughout the whole gait cycle. Participants showed greater increase in medial hamstring muscle activity in the paretic leg and improved step length symmetry after the removal of targeted resistance force, compared to effects of a constant resistance force (P < 0.03). In addition, treadmill walking with the targeted resistance induced more symmetrical step length during overground walking 10 min after the treadmill walking, compared to the result of the constant resistance force (P = 0.01). Applying a targeted resistance force to the pelvis during the stance phase of the paretic leg may induce an enhanced use of the paretic leg and an improvement in gait symmetry in individuals post-stroke. These results provide evidence showing that applying a targeted resistance to the pelvis may induce a forced use of the paretic leg during walking.